The ionospheric scintillation phenomenon - (:unkn) unknown (My University, 2022)
The SAGAIE network was deployed in West-Africa in 2013 to assess the feasibility of an equatorial for ASECNA SBAS by studying ionospheric scintillation. This study of the network’s measurements, taken between 2013 and 2016, analyzes the characteristics of the scintillation recorded by five receivers that cover Sub-Saharan West-Africa.
Keywords: African Research